Myeloma Propagating Cells, Drug Resistance and Relapse. (28th September 2015) - Karadimitris, Anastasios; Chaidos, Aristeidis; Caputo, Valentina; Goudevenou, Katerina; Ponnusamy, Kanagaraju; Xiao, Xiaolin
Abstract Multiple myeloma (MM) is an incurable tumor of the plasma cells, the terminally differentiated immunoglobulin secreting B lineage cells. The genetic make‐up of MM has been extensively characterized but its impact on the biology of the disease is incomplete without more precise knowledge of the identity and functional role of cells with multiple myeloma propagating activity (MMPA). We review here recent data that link MMPA with myeloma clonotypic populations organized in a cellular hierarchy that mirrors normal B cell development and also with drug resistance and disease relapse. We further propose a conceptual framework which, with optimal use of recent technological advances in genomics and phenomics, could allow dissection of the cellular and molecular properties of cells with MMPA, drug resistance and in vivo relapse in an integrated and patient‐specific manner. There is real hope that these approaches will significantly contribute to further improvements in disease control, overall survival, and possibly cure of patients with MM. Stem Cells2015;33:3205–3211